2016
DOI: 10.1037/dev0000068
|View full text |Cite
|
Sign up to set email alerts
|

Effects of viewing relational aggression on television on aggressive behavior in adolescents: A three-year longitudinal study.

Abstract: Most researchers on media and aggression have examined the behavioral effects of viewing physical aggression in the media. Conversely, in the current study, I examined longitudinal associations between viewing relational aggression on TV and subsequent aggressive behavior. Participants included 467 adolescents who completed a number of different questionnaires involving media and aggression at 3 different time points. Results revealed that viewing relational aggression on TV was longitudinally associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 71 publications
1
34
0
Order By: Relevance
“…Finally, consistent with prior research in other populations, caregivers described the importance of and barriers to both monitoring and mediating media content with YFC (Collier et al, ; Coyne, ; Padilla‐Walker et al, ). Barriers described were similar to those found in studies involving other youth populations, but are likely to be amplified by factors such as a lack of familiarity or trust bond with a youth in their home or encountering defiant or oppositional youth.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Finally, consistent with prior research in other populations, caregivers described the importance of and barriers to both monitoring and mediating media content with YFC (Collier et al, ; Coyne, ; Padilla‐Walker et al, ). Barriers described were similar to those found in studies involving other youth populations, but are likely to be amplified by factors such as a lack of familiarity or trust bond with a youth in their home or encountering defiant or oppositional youth.…”
Section: Discussionsupporting
confidence: 78%
“…Participants cited numerous ways in which media influences youth norms and attitudes around romantic and sexual behaviour, beauty and physical appearance, and idealizations of family life. Consistent with research on other groups of youth, participants also perceived impacts on youth behaviour, such as engagement in risky sexual behaviours, viewing of pornography, and connection with predators and/or risky peers (Bailin et al, ; Brown et al, ; Chandra et al, ; Coyne, ; Exelmans et al, ).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Previous studies have found that poor emotion regulation, inflated self-views, certain forms of internalizing and externalizing psychopathology, media exposure to relational aggression, and experiencing child abuse/maltreatment can influence youth to relationally aggress against other children (Archer & Coyne, 2005; Card et al, 2008; Cook et al, 2010; Coyne, 2015; Cullerton-Sen et al, 2008; Kawabata et al, 2011; Mayeux, 2014; Miller & Lynam, 2003; Nelson & Crick, 2002; Ojanen, Findley & Fuller, 2012; Ostrov & Houston, 2008; Tackett et al, 2014; Underwood, Beron & Rosen, 2011). In contrast, researchers have found that victims of relational aggression often lack social skills and have difficulty resolving social problems (Archer & Coyne, 2005; Champion, Vernberg, & Shipman, 2003; Cook et al, 2010), but these pathways are complex and more poorly understood than pathways to perpetration.…”
mentioning
confidence: 99%
“…We also hypothesized aggressiveness increases when participants were passively exposed to media violence. Merely observing violence also increases aggressiveness in the short and long run (e.g., Anderson et al, 2003;Coyne, 2016;Gentile et al, 2011).…”
Section: Overview and Hypothesesmentioning
confidence: 99%